Melatonin receptors and Per1 expression in the inferior olivary nucleus of the Sapajus apella monkey - Granado, Marcos Donizete Junior; Pinato, Luciana; Santiago, Jeferson; Barbalho, Sandra Maria; Parmezzan, Jessica Ellen Lima; Suzuki, Lenita Mayumi; Cabrini, Mayara Longui; Spressão, Daniele Raineri Mesquita Serva; Carneiro de Camargo, Ana Letícia; Guissoni Campos, Leila Maria (Frontiers in Neuroscience, 2022)
Melatonin is a transducer of photic environmental information and participates in the synchronization of various physiological and behavioral phenomena. Melatonin can act directly in several areas of the central nervous system through its membrane receptors coupled to G protein, called MT1 and MT2 receptors. In some structures, such as the retina, hypothalamus and pars tuberalis, the expression of both melatonin receptors shows circadian variations. Melatonin can act in the synchronization of the clock proteins rhythm in these areas. Using the immunohistochemistry technique, we detected the immunoexpression of the melatonin receptors and clock genes clock protein Per1 in the inferior olivary nucleus (ION) of the Sapajus apella monkey at specific times of the light-dark phase. The mapping performed by immunohistochemistry showed expressive immunoreactivity (IR) Per1 with predominance during daytime. Both melatonin receptors were expressed in the ION without a day/night difference. The presence of both melatonin receptors and the Per1 protein in the inferior olivary nucleus can indicate a functional role not only in physiological, as in sleep, anxiety, and circadian rhythm, but also a chronobiotic role in motor control mechanisms.